Iron and copper on Botrytis cinerea: new inputs in the cellular characterization of their inhibitory effect - Rodríguez-Ramos,Fátima; Briones-Labarca,Vilbett; Plaza,Verónica; Castillo,Luis (PeerJ, 2023)
Certain metals play key roles in infection by the gray mold fungus, Botrytis cinerea. Among them, copper and iron are necessary for redox and catalytic activity of enzymes and metalloproteins, but at high concentrations they are toxic. Understanding the mechanism requires more cell characterization studies for developing new, targeted metal-based fungicides to control fungal diseases on food crops. This study aims to characterize the inhibitory effect of copper and iron on B. cinerea by evaluating mycelial growth, sensitivity to cell wall perturbing agents (congo red and calcofluor white), membrane integrity, adhesion, conidial germination, and virulence. Tests of copper over the range of 2 to 8 mM and iron at 2 to 20 mM revealed that the concentration capable of reducing mycelial growth by 50% (IC50) was 2.87 mM and 9.08 mM for copper and iron, respectively. When mixed at equimolar amounts there was a significant inhibitory effect mostly attributable to copper. The effect of Cu50, Fe50, and Cu50–Fe50 was also studied on the mycelial growth of three wild B. cinerea strains, which were more sensitive to metallic inhibitors. A significant inhibition of conidial germination was correlated with adhesion capacity, indicating potential usefulness in controlling disease at early stages of crop growth. Comparisons of the effects of disruptive agents on the cell wall showed that Cu, Fe, and Cu–Fe did not exert their antifungal effect on the cell wall of B. cinerea. However, a relevant effect was observed on plasma membrane integrity. The pathogenicity test confirmed that virulence was correlated with the individual presence of Cu and Fe. Our results represent an important contribution that could be used to formulate and test metal-based fungicides targeted at early prevention or control of B. cinerea.
Keywords: Botrytis cinerea; Iron; Copper; Antifungal characterization; Metals; Fungitoxicity